Prevalence and Determinants of Depression among Women with Breast Cancer in Middle Euphrates Cancer Center in Najaf Province -Iraq - Shaymaa Abdul Lateef Alfadhul (مجلة الكوفة الطبية)
Background: Breast cancer (BC) is the most prevalent cancer among women worldwide. The psychosocial consequences of illness among women with BC are so frequent that they result in depression and other psychological distress.